Disruptions In the Modern Economy and Their Consequences On The Functioning of Supply Chains - Olena SHANDRIVSKA; Irena PAWŁYSZYN (Communications of International Proceedings, 2024)
Disruptions such as pandemics, geopolitical conflicts, or natural disasters can severely disrupt supply chains, causing delays and shortages. It can lead to destabilization of economies, price increases, and disruptions in the availability of key products worldwide. Therefore, identifying the dimensions of supply chain transformation in times of disruption is seen as an important economic challenge due to the growing threats to the economic security of countries and, in particular, their logistics sectors. The objective of the article is to identify the main disruptions that destabilize global supply chains and supply chains in Ukraine, investigate the nature of disruptions and structure them. The chosen disruptions are the spread of the COVID-2019 pandemic, the RF war in Ukraine, the anticipation of a global food crisis, and inflationary expectations. To achieve the goal general scientific and special methods were used, in particular, a bibliometric analysis, dialectical and abstract-logical methods to generalize the theoretical and methodological foundations of the functioning of the world economy and its reflection in the functioning of global supply chains and the Ukrainian logistics sector under the influence of various types of disruptions. The analysis carried out presents in detail the challenges supply chains are currently facing, the adaptation mechanisms necessary to overcome or reduce the impact of disruptions in relation to supply chains, and the tasks logistics should meet in the context of individual disruptions. The research indicates the need to transform one of the most important links in the economy, which are transportation systems and supply chains.
Keywords: supply chains; disruption; COVID-2019; war; transport; cargo; economy.